Georadar surveys of the flooring in the St. Francis of Assisi basilica in Krakow - Łyczak, Monika; Adamiec, Jacek; Skupień, Tomasz; Małysa, Tomasz; Groffik, Anna (Geology, Geophysics and Environment, 2018)
Basilica of St. Francisco of Assisi together with the buildings of the Franciscan convent constitute one of the most important points on the map of medieval Krakow. However, their architectural transformations are still not well recognized. In 2015, the opportunity to expand this knowledge occured. Within the basilica itself, along with the adjacent chapels, a comprehensive, non-invasive, georadar floor examination was held. Its effect, apart from confirming the location of known tombs and burial crypts, was the discovery of completely unknown underground rooms. Using small-hole drills, the rooms were recognized as burial crypts. Currently, their diagnosis is conducted by archaeological methods. The presented case study was also an occasion to describe explicitly the methodological bases of crypt identification practice, using connection between some specific construction details characteristic for ancient European architecture and the corresponding GPR manifestations (diagnostic features).